1995
DOI: 10.1097/00005392-199511000-00039
|View full text |Cite
|
Sign up to set email alerts
|

Preference, Compliance and Initial Outcome of Therapeutic Options Chosen by Female Patients with Urinary Incontinence

Abstract: When given options, patients chose nonoperative measures first. Compliance was poor among patients who chose behavioral modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Wyman et al [1998] reported a high level of initial compliance with a pelvic muscle exercise regimen, which had fallen by 20% at 3 months. A study by Diokno and Yuhico [1995] found that compliance, in women choosing among three types of incontinence management, was poor for those choosing exercises in comparison to those selecting medication and surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Wyman et al [1998] reported a high level of initial compliance with a pelvic muscle exercise regimen, which had fallen by 20% at 3 months. A study by Diokno and Yuhico [1995] found that compliance, in women choosing among three types of incontinence management, was poor for those choosing exercises in comparison to those selecting medication and surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The cure rates have been approximately 70%-90% [87]. However, these operations can cause complications such as bleeding, pelvic pain and voiding difficulties [88], and only 14% of patients prefer surgical treatment [89]. The first-choice conservative treatment is exercise to strengthen the pelvic floor muscles, but its cure rate is as low as 12%-13% [88,89] and the dropout rate is high [89].…”
Section: Discussionmentioning
confidence: 99%
“…However, these operations can cause complications such as bleeding, pelvic pain and voiding difficulties [88], and only 14% of patients prefer surgical treatment [89]. The first-choice conservative treatment is exercise to strengthen the pelvic floor muscles, but its cure rate is as low as 12%-13% [88,89] and the dropout rate is high [89]. In drug therapy, c~-antagonists [90,91] and tricyclic depressants [92], which act to enhance the contractility of the smooth muscles, are used.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs, hormonal replacement therapy, mechanical support devices, rehabilitation of pelvic floor and electrical stimulation are some of the treatment alternatives to surgery 10) . Even though the cure rates of surgery in genuine stress incontinence was reported as 70-90%, according to the results of a questionnaire, only 14% of patients prefer surgical treatment 7,11) . The first step of conservative treatment is pelvic floor exercises to strengthen pelvic floor muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent voluntary contractions can be seen after optimal application of Kegel exercises 7) . But its cure rate was reported as 12-13% and the number patients refusing to continue treatment is quiet high 9,11) . Biofeedback is a method which increases the success of Kegel exercises by making the patients sense the contractions using audio or visual devices 12) .…”
Section: Discussionmentioning
confidence: 99%